Combination with Toll-like receptor 4 (TLR4) agonist reverses GITR agonism mediated M2 polarization of macrophage in Hepatocellular carcinoma. (31st December 2022) - Pan, Caixu; Wu, Qinchuan; Wang, Shuai; Mei, Zhibin; Zhang, Lele; Gao, Xingxing; Qian, Junjie; Xu, Zhentian; Zhang, Ke; Su, Rong; Guo, Danjing; Zhou, Lin; et al.
ABSTRACT: The glucocorticoid-induced tumor necrosis factor receptor (GITR) agonistic antibody (DTA-1) has been proved to elicit robust immune response in various kinds of tumors. However, only a few of the HCC patients could benefit from it, and the mechanism of DTA-1 resistance remains unknown. Here, we measured GITR expression in different immunocytes in HCC microenvironment, and we observed that tumor-infiltrating regulatory T cells (Ti-Tregs) significantly expressed GITR, which were associated with poor prognosis. Meanwhile, we analyzed the variation of tumor-infiltrating immune components and associated inflammation response after DTA-1 treatment in orthotopic liver cancer model of mice. Surprisingly, DTA-1 treatment reduced the infiltration of Tregs but failed to activate CD8 + T cells and elicit antitumor efficacy. In particular, DTA-1 treatment enforced alternative M2 polarization of macrophage, and macrophage depletion could enhance DTA-1-mediated antitumor efficacy in HCC. Mechanistically, macrophage M2 polarization attributed to the IL-4 elevation induced by Th2 immune activation in the treatment of DTA-1, resulting in DTA-1 resistance. Furthermore, Toll-like receptor 4 (TLR4) agonist could diminish the macrophage (M2) polarization and reverse the M2-mediated DTA-1 resistance, eliciting robust antitumor effect in HCC. Our finding demonstrated that the TLR4 agonist synergized with DTA-1 was a potential strategy for HCC treatment.